Vanishing headache in a young female: An interesting case report - Balasubramanian, D; Chandramouleeswaran, V; Balasubramanian, S; Narasimhan, R Lakshmi; Kannan, V; Nithyanandam, A; Venkatesan, S (Indian Journal of Case Reports, 2019)
Headache is one of the most common neurological symptom occurring worldwide. Here, we present a unique case of secondary headache in a young female which got reversed with appropriate treatment. A young female who presented with a severe subacute unilateral left-sided intractable headache with papilledema and obstructive hydrocephalus was found to have 4th ventricular neurocysticercosis causing obstruction of the foramen of Magendi and Luschka, relieved on timely surgical excision and with medical management. This case is reported to highlight the rare causes of secondary headache and various presentations of neurocysticercosis, in endemic areas like India as it causes neurological morbidity which can be alleviated on appropriate treatment, thereby preventing economic hardship and improving the quality of life.